AFIKSASI BAHASA TALIABU DIALEK MANGE - Umiatun Sa’diyah; Gede Sidi Artajaya (Stilistika : Jurnal Pendidikan Bahasa dan Seni, 2023)
The Taliabu language of the Mange dialect is one of the regional languages in the Taliabu Island Regency, North Maluku Province. The Taliabu language of the Mange dialect also has affixations in the structure of its language. This study aims to determine the types of affixes or affixations found in the Taliabu language of the Mange dialect. The method of providing data in this study is to use the capable method. The data analysis method in this study is to use the intralingual matching method. The result of this study is that the Taliabu language of the Mange dialect has one prefix, three prefixes, and one suffix.